Noctiluca Scintillans (Macartney) Kofoid & Swezy Bloom Off Gadani Ship Breaking Area of Northern Arabian Sea, Baluchistan - Hamid, Tayyaba; Shoaib, Nafisa; Qadir , Venus A; Ahmed Siddiqui, Pirzada Jamal (Bangladesh Journal of Botany, 2022)
The Noctiluca scintillans (Macartney) Kofoid & Swezy a dinoflagellate of marine environment can form bloom and generates substances that are noxious to aquatic organisms. An intense bloom of the N. scintillans in Gadani, Baluchistan coast along Northern Arabian Sea is reported in the present study. Sea water was collected using Niskin water sampler from three locations for water quality and nutrient analysis. Maximum number (6780 cells/l) of phytoplankton cells were observed in Station-I than that of Station-II (4180 cells/l) and in Station III (3580 cells/l). Maximum number (2740 cells/l) of Noctiluca was observed in station I than station II (1020 cells/l) and minimum (620 cells/l) in Station III. Among toxic species of dinoflagellates, Alexandrium tamaresence, Ceratium fusus, Dinophysis caudata, Gyrodinium spirale, Prorocentrum micans, Prorocentrum arcuratum and Scrippsiella trochoidea were observed. The Noctiluca scintillans can transfer toxins to higher trophic levels by grazing these toxic dinoflagellates. The increase in intensity of algal blooms occurring in marine waters cause detrimental effects including bio toxins, physical damage and the anoxia which caused massive fish mortality, affect fishery resources, biodiversity and vulnerable to the aquatic ecosystem. Bangladesh J. Bot. 51(3): 507-517, 2022 (September)